2021 IEEE/ACM International Symposium on Code Generation and Optimization (CGO) 2021
DOI: 10.1109/cgo51591.2021.9370305
|View full text |Cite
|
Sign up to set email alerts
|

Memory-Safe Elimination of Side Channels

Abstract: Agradeço ao professor Luís Fabrício Wanderley Góes, meu orientador durante a graduação. Foi por meio dele que passei a conhecer o professor Fernando Magno Quintão Pereira, que hoje é meu orientador no mestrado. Ao professor Fernando, por todo o suporte e por todos os ensinamentos durante estes últimos dois anos. É, certamente, uma grande fonte de inspiração, como pesquisador, professor, orientador e como pessoa. Sem ele, nada do que foi desenvolvido neste projeto seria possível. Aos meus colegas do Laboratório… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…These numbers only increase to 16% and 68% for word-level protection. Our SCE suite numbers are comparable to those of SC-Eliminator [78] and Soares et al [60] (which we confirmed using the artifacts publicly released with both papers, Appendix G), despite Constantine offering much stronger compatibility (i.e., real-world program support) and security (i.e., generic data-flow protection and no decoy path side channels) guarantees. On the Raccoon test suite, on the other hand, Raccoon reported two orders-of-magnitude slowdowns (up to 432x) on a number of benchmarks, while Constantine's worst-case slowdown in its default configuration is only 1.84x, despite Constantine again providing stronger compatibility and security guarantees (i.e., no decoy path side channels).…”
Section: Performance Evaluationsupporting
confidence: 79%
See 4 more Smart Citations
“…These numbers only increase to 16% and 68% for word-level protection. Our SCE suite numbers are comparable to those of SC-Eliminator [78] and Soares et al [60] (which we confirmed using the artifacts publicly released with both papers, Appendix G), despite Constantine offering much stronger compatibility (i.e., real-world program support) and security (i.e., generic data-flow protection and no decoy path side channels) guarantees. On the Raccoon test suite, on the other hand, Raccoon reported two orders-of-magnitude slowdowns (up to 432x) on a number of benchmarks, while Constantine's worst-case slowdown in its default configuration is only 1.84x, despite Constantine again providing stronger compatibility and security guarantees (i.e., no decoy path side channels).…”
Section: Performance Evaluationsupporting
confidence: 79%
“…The just-in-time strategy to linearize secret-dependent unbounded control flows (loops) allows us to dodge intractability with high bounds and code bloat with tractable instances [60]. For points-to set identification and indirect call promotion, our analyses yield very accurate results (i.e., closely matching the run-time accesses) on the programs we consider.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations